As crianças e suas relações com a Escola Diferenciada dos Pitaguary - Sousa, Flávia Alves de (2007)
This research makes a discussion about the relation of the children with the knowledge teaches in the “escola indígena dos Pitaguary”, mainly on what we call “differenced acquaintance”. I intend be able to interpret how the children comprehend this knowledge teaches on this “differenced school”, which significations are in the enounced ideas by the social agents about “be índio”; that is, the children reproduce the discursive and no discursive practices inherent to “be índio” or they produced your own signification? If they produced, how do they? Therefore, I consider the Foucault’s idea (1979), the subjects are effects of the discursive practises, where are included knowledge/power relation. My great question is think the identity and the difference like the battlefield among different significations, as much on the theory ambit (the idea of the difference on the deleuzian Philosophy and on the Social Science), as on the social practices related to discusses symbolic experiences of the Pitaguary adults and children. While the adults understand the school like the place where the children go to learn and be the “future Pitaguary”, the “true Pitaguary”, the children produce others perceptions about “be índio”. For children, the “true índio” correspond to a stereotype model, but they do not identify themselves with this kind of índio, therefore these children construct another way to identify themselves like a índio: “we do not true índios, we are false índios”. The watched schools are localized on the Maracanaú, a municipal district in the “Grande Fortaleza”. I worked with the Escola Indígena de Ensino Diferenciada Chuy (at the “Horto Florestal”) and the Escola de Educação Básica do Povo Pitaguary (at the Santo Antônio dos Pitaguary). The empiric datum were collected from observations at the classrooms, semi-structured interviewers with the parents and teachers, and not structured interviewers with some children who study at the first and second degrees; and I did, too, oriented activities with the children, working with pictures and photos.